Estilos parentales y problemas de regulación emocional en adolescente de 15 a 18 años de la Unidad Educativa - Gutierrez Calle, Ariel Fabian (2025)
The present research aims to analyze the relationship between parenting styles and emotional regulation problems in a specific group of adolescents. By implementing the Chi-square correlation coefficient, it was possible to examine the responses obtained through the applied psychometric tests, including the DERS (Difficulties in Emotion Regulation Scale) questionnaire, in relation to the four existing parenting styles: authoritative, authoritarian, permissive, and neglectful. The results demonstrated that there is no significant correlation, within the evaluated sample, between parenting styles and emotional regulation problems. This is because the obtained p-value was 0.25, which is higher than the significance threshold of 0.05. However, a slight significance was observed in some responses. It is incorrect to affirm that parenting styles decisively influence the development of emotional regulation problems in adolescents, suggesting that other factors play a role in the development of these difficulties, beyond parenting styles.